Knowledge and use of Silver Diamine Fluoride (SDF) by dentists in Lahore: A cross-sectional study - Palwasha Babar, Uswa Qaiser, Hussain Ahmed, Arfa Sarwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Silver Diamine Fluoride (SDF) has emerged as a promising alternative to the traditional caries management concept of ‘drill and fill’. It offers a conservative, inexpensive, painless and simple way to stop caries progression. Aim: To assess the knowledge and use of Silver Diamine Fluoride among dental practitioners in Lahore. Methodology: A cross-sectional study was conducted after getting institutional ethical approval. A pre-validated questionnaire was used to collect data from 186 dental practitioners. Data was analyzed using SPSS V 25. Results: Among the participants, 101(54.3) were females and 83(44.6%) were males. 30.6% and 47.8% of the participants strongly agreed and agreed to the use of SDF to arrest cavitated lesions. Regarding the barriers in SDF usage, permanent black discoloration was chosen by 70.4%, concern over patient satisfaction by 55.7% and the fact that SDF not restoring tooth anatomy if it is not followed by a restoration by 40.3% of the participants. 72.6% of the participants reported that they have never used SDF, 20.2% sometimes and 7.2% often use SDF. 55.9% of the participants expected an increase infuture usage of SDF. Conclusion: Dentists have a fair knowledge about the use of SDF and its application in clinical practice. However, there is disparity in its use among the dental practitioners due to the black discoloration and concern over parental acceptance. Keywords: Minimally invasive; Silver Diamine Fluoride; Caries arrest